The Relationship Between Provetella Genus in Intestinal Flora and Exercise and Diet Styles of Professional Football Players - Çelik, Akın (Progress in Nutrition, 2021)
Aim: This study aims to deal with the relationship between Provetella genus in intestinal flora and exercise and dieting styles of professional football players. Material and Method: 10 volunteers, 5 male fotballers playing at elite level and 5 sedentary men between the ages of 18-21, participated in the study. In the study, metagenomic analysis of Prevotella genus was performed by taking “Stool Sample” from the subjects only for 1 time. A questionnaire was applied to determine the nutritional styles of the subjects. SPSS 20.0 package program and Minitab 17 programs were used in the statistical analysis of the data, and the significance level was taken as p